Profile of hospital admissions for adults with cerebral palsy: a retrospective cohort study. (1st April 2020) - Morgan, Prue; Enticott, Joanne; Nikam, Rujuta; Tracy, Jane
Abstract : Aim: To retrospectively profile acute hospital admissions for a defined cohort of adults with cerebral palsy (CP). Method: Five years of health service data were interrogated to identify acute health service use by adults with CP. Admission types were described, admission reasons categorized using International Classification of Diseases, 10th Revision codes, and length of stay (LOS) calculated. Any differences between paediatric and adult subsets were explored. Results: Individuals with CP constituted 2922 admissions. Of these, 850 (29%) were adult admissions. There were significant differences between admission reasons for paediatric and adult cohorts, with adults predominantly seeking hospital admission for emergency rather than planned care (emergency reason: adults 62.1%, paediatrics 25.2%; p <0.001). The median adult admission LOS was longer than that of children ( p <0.001). The primary diagnosis admission reason in the adult data set was respiratory illness (20%) followed closely by gastrostomy dysfunction (19%). Interpretation: Adults with CP predominantly access acute hospital services for emergency health care. A high frequency of admissions is associated with respiratory illness and gastrostomy dysfunction in adults with CP. What this paper adds Adults with cerebral palsy (CP) access acute inpatient services for emergency health care. Hospital admissions are predominantly because of respiratory illness and gastrostomy dysfunction. Admission length of stay is longer for adults than children. Many adults with CP require hospitalization more than once a year. Abstract : What this paper adds Adults with cerebral palsy (CP) access acute inpatient services for emergency health care. Hospital admissions are predominantly because of respiratory illness and gastrostomy dysfunction. Admission length of stay is longer for adults than children. Many adults with CP require hospitalization more than once a year. This article is commented on by Yu, Coller, and Kind on page 889 of this issue.